The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

Interactions of Micro/Nanoplastics and Antibiotics: Research Trends, Toxicological Effects, and Environmental Risks - Junyi Du; Jia Du; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Jianjun Chen; Weihong Wu (Water, Air, & Soil Pollution, 2026)

Boosting CO₂ sequestration and lipid production in microalgae via a dual-ligand MOF bio-hybrid strategy - Longfei Yuan; Mengwei Li; Xinqing Gao; Manrong Wu; Yitong Wu; Yiming Li; Jianjun Liao; Ping Zhang; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Arbuscular mycorrhizal fungi improve the mechanical properties of root–soil composites of different vegetation types in a loess subsidence area - Wenbo Zhu; Yinli Bi; Chao Wu; Linlin Xie; Zengming Ke; Jinduo Chen (Rhizosphere, 2026)

Excitation force in a two-stage pump-jet propulsor: The modulation effect via the rotor phase angle - Jiansheng Zhang; Linlin Cao; Min Chai; Dazhuan Wu; Shuihua Zheng (Ocean Engineering, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Experimental investigation on the squeeze deformation and failure mechanisms of tunnel invert in high ground stress stratified soft rock and directional reinforcement measures - Wenbo Yang; Linlin Yang; Zhongyuan Xing; Wenyu Xu; Chaofan Yao; Fangyin Wu; Yuxiang Huan (Tunnelling and Underground Space Technology, 2026)

Cellulose sulfate-modified biochar loaded with Rs-2 for improving saline-alkali soil - Linlin Zhu; Yao Chen; Nana Liu; Yanhui He; Xiaochen Liu; Qiuyu Chen; Fei Tian; Zhansheng Wu (Soil and Tillage Research, 2026)

Co-combustion of municipal solid waste and antibiotic fermentation residue: Gaseous pollutant emissions and ash slagging characteristics - Changhong Huang; Yuhang Du; Lei Bei; Jiaxing Du; Wu Yang; Ben Wang; Linlin Xu; Lushi Sun (Fuel, 2026)

An accelerated XFEM framework for fatigue crack propagation analysis of shield tunnel linings subjected to cyclic train loads - Wenbo Yang; Zhenian Wang; Linlin Yang; Ziyuan Su; Yang Zhou; Chaofan Yao; Fangyin Wu (Computers and Geotechnics, 2026)

Enzymatic synthesis of oligodextran with prebiotic potential by a recombinant dextransucrase from Latilactobacillus sakei L3 - Binbin Wang; Linlin Hao; Kaiyue Zuo; Xiaojing Liu; Huimin Yao; Weizhong Liu; Fangkun Zhao; Lei Pan; Baomei Wu (Carbohydrate Polymers, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Mechanisms of broadband force generation and efficient prediction for a pump-jet propulsor - Jianwei Zhang; Xinli Jin; Jianping Cheng; Duo Xiang; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2026)

Ecoenzymatic stoichiometry reveals higher microbial nitrogen limitation in active than passive restored alpine wetlands - Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Abraham Allan Degen; Akash Tariq; Feida Sun; Jinchao Gong; Shijie Zhou; Yue Xiu; Linlin Li; Liang Tie; Jordi Sardans; et al. (Journal of Environmental Management, 2026)

An NDVI-constrained multi-source remote sensing data fusion network for detecting the level of larch caterpillar (Dendrolimus superans) infestation - Linlin Wu; Mingchang Wang; Fengyan Wang; Dehua Mao (Journal of Mountain Science, 2026)

Identification of Fertility and Internal Genetic Uniformity in Monogerm Sugar Beet Hybrid Combinations - Chengwei Zhang; Rui Gao; Gaofei Lü; Zedong Wu; Linlin Sun (Sugar Tech, 2026)

Distributed three-dimensional target enclosing control for AUVs under ocean currents - Linlin Shi; Haoming Wu; Biao Wei; Simin Lv; Yang Xu; Ronghao Zheng; Yu Chen (Ocean Engineering, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Multi-measure ecological restoration drives phytoplankton succession and shifts community assembly in an urban eutrophic lake - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Fan Xun; Weixiang Ren; Mengdie Zhou; Chenxin Zhong; Chunyan Xiao; Linlin Lei (Ecological Engineering, 2026)

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

FAdV-4-induced secondary Pasteurella multocida infection potentiates bacterial adherence and aggravates pathological damage in SPF chickens - Yuxin Chen; Guizhen Yi; Yunzhen Huang; Linlin Li; Jiawen Dong; Yong Xiang; Minhua Sun; Junqin Zhang; Bin Wu (Veterinary Microbiology, 2026)

The role of microplastics in bioavailability and toxicity of triclosan in the soil-earthworm system: Inhibitor or facilitator - Xian Chen; Jingcheng Liang; Linlin Shi; Shipeng Luo; Rong Ji; Jiehong Cheng; Ying Wu; Yuchen Wang (Journal of Environmental Chemical Engineering, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

Source and accumulation of helium in the Dongsheng gas Field, Ordos Basin, China: Insights from noble gas isotopes - Yu Gao; Shuangjian Li; Xiaoqi Wu; Dongya Zhu; Pengpeng Li; Linlin Wang; Guangxiang Liu; Jiahao Lv; Jiarun Liu; Quanyou Liu (Journal of Asian Earth Sciences, 2026)

Occurrence, composition profiles, and human exposure assessment of liquid crystal monomers in indoor dust from Wuxi, China - Yiyang Yao; Linlin Wu; Run Zhou; Xi Wang; Yan Gong; Rong Chen; Wenwei Liu (Environmental Pollution, 2026)

Deubiquitinases in liver diseases: from mechanisms to targeted therapy - Zhenge Zhang; Wanli Duan; Yixiang Wang; Peng Hao; Linlin Chen; Ziyi Hao; Ming He; Yingli Wu; Hao Luo (Science China Life Sciences, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Oxygen vacancy induced strong interaction of single atom Ru with In2O3 for improved CO2 hydrogenation to methanol - Shilong Xiong; Song He; Linlin Wu; Haibo Zhao; Chang-jun Liu (Chemical Engineering Journal, 2026)

Hydrodynamics, mixing performance and power consumption in horizontal millimeter-scale helical tube reactors: comprehensive experimental and numerical investigations across a wide range of centrifugal-to-gravitational acceleration ratio - Zhongyao Zhang; Yuanjie Wu; Xiaopeng Chen; Jiezhen Liang; Qianyun Tan; Chenghong Wu; Bo Feng; Denghan Luo; Linlin Wang (Chemical Engineering Journal, 2026)

Meso–Neoproterozoic rift system along the southwestern North China Craton: evidence from recent drilling and seismic data - Zhenhong Li; Xiaopeng Dong; Haifeng Bai; Yijun Zhou; Jiawei Cui; Linlin Kou; Fang Wu (International Geology Review, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Engineered microbial consortium enhances tomato salt tolerance through rhizosphere modulation for sustainable crop production - Linlin Sun; Xinyu Jia; Xiaohu Zhou; Junsong Yue; Zihe Deng; Muhammad Saad Ahmed; Xiaochen Liu; Zhansheng Wu (Journal of Cleaner Production, 2026)

Bias-aware learning for unbiased scene graph generation in remote sensing imagery - Tingzhu Wang; Linlin Wang; Junwei Luo; Kang Wu; Yansheng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Bisphenol S and Neurological Health: An Integrated Overview of Neurotoxicity and Underlying Mechanisms - Xing Zhang; Linlin Wu; Dingqi Hua; Bin Zhang; Xi Wang; Linchang Li; Yi Wang; Jiangbo Zhu (Molecular Neurobiology, 2026)

Biodiversity and biogeographic patterns of Nereididae (Annelida) across the Indo-Pacific Convergence Zone - Jieyang Weng; Xuwen Wu; Tiantian Wang; Chenrui Li; Linlin Zhang (Journal of Oceanology and Limnology, 2026)

Research hotspots and trends in Spartina alterniflora studies (1970–2023): A bibliometric analysis - Dandan Yan; Shanshan Wang; Peng Song; Yuqing Zhang; Yiming Huang; Yu Wang; Wenyan Zhu; Linlin Wu (Marine Pollution Bulletin, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

A shift toward extensive utilization: The long-term relations between building volume and utilization intensity in China’s 267 natural cities - Kechao Wang; Linlin Ruan; Wu Xiao; Runjia Yang; Jiatong Zhou (Landscape and Urban Planning, 2025)

Aminated lignin-modified polyethersulfone membranes with enhanced antifouling performance for oil-water separation - Linlin Liang; Meijiao Peng; Hui Xu; Zijun Wu; Baojie Liu; Chengrong Qin; Chen Liang; Caoxing Huang; Shuangquan Yao (Journal of Environmental Chemical Engineering, 2025)

Transcriptomic analysis of mature biofilm and planktonic cells of Listeria monocytogenes under nutritional stress - Yuan Wang; Linlin Xiao; Jing Ji; Danial Hassani; Youzhi Wu; Hongmei Niu; Qingli Dong (Food Microbiology, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

The Impact of Microplastics on the Dissemination, Persistence, and Ecotoxicological Effects of Antibiotic Resistance Genes in Terrestrial Ecosystems - Jia Du; Tingting Chen; Luxi Niu; Lanxue Zhi; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Weihong Wu (Water, Air, & Soil Pollution, 2025)

Identification for Fertility in Multigerm Sugar Beet Germplasm Resources of Molecular Markers - Jinghao Li; Linlin Sun; Zhi Pi; Shengnan Li; Zedong Wu (Sugar Tech, 2025)

Microwave-assisted modification for enhancing the slow-release performance of biochar-based fertilizer and application - Linlin Zhu; Bingzhe Su; Chen Guan; Yao Chen; Dongye Huang; Jiayao Zhou; Qiuyu Chen; Xiaochen Liu; Fei Tian; Zhansheng Wu (Journal of Soils and Sediments, 2025)

Microplastics as vectors for environmental contaminants in the food chain: Assessing the combined toxicological effects and bioavailability - Jia Du; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Weihong Wu (Toxicology Letters, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Biochar-induced strong microbial carbon limitation prompts organic carbon sequestration and plant growth in antibiotic-contaminated soil - Linlin Qiu; Tim J. Daniell; Muhammad Nafees; Yihao Chen; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Weiying Ji; Jiaying Ge; Hongyan Guo (Plant and Soil, 2025)

An MA-film platform designed for high-throughput synthesis of calcium phosphates screening amino acid on collagen film - Xiaoyu Li; Xiran Yang; Xinkun Chen; Changxia Liu; Linlin Wu; Dazhuo Qiu; Xueye Chen; Xuetao Shi (Analytica Chimica Acta, 2025)

MitoQ reducing sevoflurane-induced cognitive dysfunction by modulating mitochondrial dysfunction - Hengjie Su; Zhibin He; Haotian Wu; Linlin Wang; Huan Zhang; Siyi Yan (Metabolic Brain Disease, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

A nano-pesticide with low toxicity for earthworms obtained by immobilizing avermectin onto Mg/Al layered double hydroxides - Linlin Shi; Fengshou Dong; Jun Xu; Xiaohu Wu; Yongquan Zheng; Xinglu Pan (Environmental Pollution, 2025)

Waste asphalt-derived hard carbon assisted by biomass templating for sodium-ion batteries - Danqing Li; Xin He; Linlin Wang; Yinghao Zhang; Xingqiao Wu; Mei Ding; Chunhui Gao; Yang Gao; Chuankun Jia (Chemical Engineering Journal, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

Smartphone-assisted portable electrochemical sensing platform for point-of-care detection of thiocyanate using a laser-induced graphene composite electrode - Xiaoming Yuan; Linlin Chen; Ruwei Liu; Shilin Li; Xiu-wen Wu; Yunhan Ling (Analytica Chimica Acta, 2025)

Monitoring of Larch Caterpillar (Dendrolimus superans) Infestation Dynamics Using Time-series Sentinel Images in Changbai Mountains National Nature Reserve, Northeast China - Linlin Wu; Mingchang Wang; Jiatao Du; Jingzheng Zhao; Fengyan Wang (Chinese Geographical Science, 2025)

Holocene seismically induced soft-sediment deformation structures in the Qingshuihe Basin, northeastern Tibetan Plateau - Ting Huang; Zhenhong Li; Xiaopeng Dong; Zhonghai Wu; Linlin Kou; Fang Wu (Sedimentary Geology, 2025)

Social and ecological factors on the perception of cultural ecosystem services and disservices: Insights from Shanghai, China - Rongfei Su; Shiyu Ye; Linlin Yu; Jingbin Wu; Yan Kang; Ruishan Chen (Landscape and Urban Planning, 2025)

Zinc Deficiency Aggravates High-Fat Diet-Induced Renal Injury by Regulating Oxidative Stress and Inflammation via the Nrf2/HO-1 Pathway - Yucan Guan; Linlin Wu; Man Wu; Yuexin Zhu; Ping Luo; Manyu Luo (Biological Trace Element Research, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Study on the characteristics of an underwater vehicle pump-jet propeller under the influence of drag-reduction air - Xuanhao Shao; Jianwei Zhang; Haopeng Cai; Penglei Chen; Heng Liu; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2025)

Lactobacillus plantarum reduces polystyrene microplastic induced toxicity via multiple pathways: A potentially effective and safe dietary strategy to counteract microplastic harm - Liuting Shi; Changyin Wu; Yuye Wang; Linlin Wang; Peijun Tian; Ke-xin Shang; Jianxin Zhao; Gang Wang (Journal of Hazardous Materials, 2025)

Mechanisms for sulfadiazine effective mitigation in biochar-amended soil: From antibiotic resistance to soil microbial community composition and function - Linlin Qiu; Luxi Niu; Muhammad Nafees; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Hongyan Guo (Journal of Environmental Management, 2025)

Phospholipids and phosphoprotein-encapsulated silver nanoparticles: An eco-friendly and green antibacterial agent for killing bacteria and promoting chronic wound healing - Qian Cai; Wenting Chen; Haoying Zhang; Chuyu Tang; Songjing Zhong; Qinyu Zhao; Zhuo Wang; Chao Wu; Liugen Zheng; Yuanyuan Cheng; Linlin Li (Journal of Environmental Chemical Engineering, 2025)

Ginsenoside Rk1 Ameliorates Non-Alcoholic Fatty Liver Disease by Targeting CD36 to Modulate the AMPK Signaling Pathway - Yuqing Wu; Zhiguang Duan; Linlin Qu; Yannan Liu; Xiaoxuan Ma; Daidi Fan (Food Research International, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Recent progress in visual fire warning and protection materials - Linlin Hu; Ying Xue; Cuihong Sheng; Hailiang Wu; Yijun Yao (Chemical Engineering Journal, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Combined toxicity of decabromodiphenyl ethane and Pb on earthworms (Eisenia fetida) based on multiple biomarker responses - Meiqing Jin; Yuanchao Sun; Bing Chai; Minghu Wang; Yuping Wu; Weihong Wu; Qingwei Zhou; Linlin Qiu; Jia Du; Li Fu (Journal of Soils and Sediments, 2025)

Protective effects of resveratrol on honeybee health: Mitigating pesticide-induced oxidative stress and enhancing detoxification - Linlin Liu; Min Shi; Yanyan Wu; Jiali Hao; Junxiu Guo; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2025)

Changes in intergranular air properties and fatty acid profile of wheat bulk in a large warehouse with air-conditioned oversummering - Mengya Wang; Minghui Zhao; Xuhui Zhuang; Jianzhang Wu; Xingjun Li; Linlin Song; Yushan Jiang (Journal of Stored Products Research, 2025)

Optimized immobilization of lead and cadmium in soil using dithiocarboxy functionalized silica: A long-term effectiveness study - Mingming Lian; Chaoran Li; Longfei Wang; Liyong Niu; Linlin Zhao; Dongdong Wu; Zongsheng Zhao; Xiaohong Li; Zhijun Zhang (Journal of Hazardous Materials, 2025)

Development of a colorimetric sensor array with weighted RGB strategy for quality differentiation of Anji white tea - Qilin Xu; Xianggang Yin; Xinyi Huo; Xiaohan Zhao; Linlin Wu; Yifeng Zhou; Jun Huang (Journal of Food Engineering, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

From field to table: Reducing residual toxicity and risk of four pesticides via washing and blanching of cowpea (Vigna unguiculata (L.) Walp.) - Shuangwei Zhang; Yajing Guo; Shanshan Zhu; Linlin Guo; Xinglu Pan; Jun Xu; Fengshou Dong; Yongquan Zheng; Xiaohu Wu (Food Chemistry, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Studying the Impact of the Load Distribution Ratio on the Unsteady Performance of a Dual-Stage Pump-Jet Propulsor - Jiansheng Zhang; Ning Liang; Jianwei Zhang; Linlin Cao; Dazhuan Wu; Wei Zhao; Hanqiao Han (Journal of Marine Science and Engineering, 2025)
This study investigated the impact of different load distribution ratios between two rotors on the unsteady performance of dual-stage pump-jet propulsors using Computational Fluid Dynamics (CFDs) and experimental methods. The Shear Stress Transport (SST) k-ω model was employed to solve turbulence problems, and the numerical simulation method used was validated. The following conclusions were drawn: Different load distribution ratios of the dual-stage rotors have no significant impact on the overall propulsion performance of the propulsor. As the load distribution ratio is aft-shifted, the axial unsteady force of the entire propulsor continuously decreases, with a reduction of up to 53.6%. This is due to the gradual reduction in the energy of the first-stage rotor, leading to a more uniform Blade-Passing Frequency Velocity Harmonic Coefficient (BPFVHC) in front of the second-stage rotor, thereby gradually reducing the unsteady force of the second-stage rotor. The experimental results also indicate that the aft-shifted load model can reduce the sound pressure level of the propulsor. Compared to the prototype propulsor, the sound pressure level at the Blade-Passing Frequency decreases by 6.67 dB, or about 78.5%, in sound energy. This study has important implications for the low-excitation design of dual-stage pump-jet propulsors.

Innovative citric acid/polydopamine@sepiolite composites for efficient removal of Ni2+ and methylene blue in single and binary adsorption systems: Regulation and mechanism - Linlin Liang; Zefeng Ge; Wu Lei; Fengyun Wang; Mingzhu Xia; Zhihui Wang (Journal of Environmental Chemical Engineering, 2025)

An experimental study of heat transfer in pulsed fluidised beds via infrared thermography - Shuxian Jiang; Linlin Xu; Kaiqiao Wu; Victor Francia; Marc-Olivier Coppens (Chemical Engineering Journal, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Antifungal activity and active compound identification of Myrothecium spp. against grape anthracnose and gray mold - Linlin Gao; Yijie Zhai; Jiajia Wu; Yuwei Li; Yanchun Fan; Junqiang Guo; Xiping Wang; Zhi Li (Pesticide Biochemistry and Physiology, 2025)

An expert-demonstrated soft actor–critic based adaptive trajectory tracking control of Autonomous Underwater Vehicle with Long Short-Term Memory - Yuxuan Wang; Yaochun Hou; Zhounian Lai; Linlin Cao; Weirong Hong; Dazhuan Wu (Ocean Engineering, 2025)

A real-time vision guidance method for autonomous longan picking by the UAV - Hengxu Chen; Kaixuan Wu; Hengyi Lin; Haobo Zhou; Zhengqi Zhou; Yuju Mai; Linlin Shi; Meiqi Zhang; Zhe Ma; Peihan Lin; Jun Li (Computers and Electronics in Agriculture, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

Using the Forel-Ule index (FUI) to track the water quality of subsidence water bodies across the life cycle of coal mining in eastern China - Wenqi Chen; Lijuan Chen; Yongping Wei; Linlin Ruan; Yanhua Fu; Wei Li; Tingting He; Wu Xiao (Journal of Environmental Management, 2025)

Lactic acid bacteria reduce polystyrene micro- and nanoplastics-induced toxicity through their bio-binding capacity and gut environment repair ability - Liuting Shi; Xin Teng; Changyin Wu; Tengxun Zhang; Xing Jin; Linlin Wang; Peijun Tian; Ke-xin Shang; Jianxin Zhao; Chitong Rao; Gang Wang (Environmental Pollution, 2025)

In2O3 modification mitigates Jahn-Teller effect in LiMn2O4 enhancing lithium extraction efficiency and stability - Linlin Chen; Linjing Fan; Delin Lan; Jun Gu; Chen Xiaojun; Haiyan Ji; Yanhong Chao; Peiwen Wu; Wenshuai Zhu (Chemical Engineering Journal, 2025)

How to optimize urban blue space to maximize its cooling benefits? A case study in megacity of Beijing - Linlin Zhang; Qingyan Meng; Shun Yao; Jiangkang Qian; Jianfeng Gao; Jiahao Wu (Building and Environment, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

A 219-year tree-ring evidence revealing the influence of the Atlantic Multi-decadal oscillation on annual mean temperature in the northern Western Sichuan Plateau - Xu Wu; Jinjian Li; Linlin Cui; Xiaofei Wu; Kaiqing Yang; Alma Lorelei de Jesus (Climate Dynamics, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

Optimization model for co-pyrolytic synergy: A case study in starch sludge with chicken manure and comprehensive investigation combining kinetics, bio-products characterization, and DFT-based decomposition pathways - Hairong Mo; Xiaopeng Chen; Tongxi Mo; Chenghong Wu; Wanbin Wei; Yuanjie Wu; Qinxin Li; Jiezhen Liang; Linlin Wang (Fuel, 2025)

Distribution of microplastics in the soils of a petrochemical industrial region in China: Ecological and Human Health Risks - Yuting Guo; Rongshan Wu; Heng Zhang; Changsheng Guo; Linlin Wu; Jian Xu (Environmental Geochemistry and Health, 2025)

Study on strengthened the Cd(II) adsorption based on co-culture of fungi and cyanobacteria - Linlin Cui; Junjun Wang; Xueling Wu; Jiaokun Li; Weimin Zeng; Guanzhou Qiu; Li Shen (Algal Research, 2025)

Towards a dialectical understanding of rural resilience and rural sustainability: bibliometric analysis and evidence from existing literature and China - Huan Li; Tao Xu; Chen Yang; Yang Fu; Changyan Wu; Linlin Zhang; Guoliang Xu; Wei Wang (Environment, Development and Sustainability, 2024)

Temperature related to the spatial heterogeneity of wetland soil total nitrogen content in a frozen zone - Linlin Wu; Mingchang Wang; Dehua Mao; Xiaoyan Li; Zongming Wang (Soil and Tillage Research, 2024)

Impact of chlorantraniliprole on honey bees: Differential sensitivity and biological responses in Apis mellifera and Apis cerana - Wenmin Li; Yikun Zan; Tong Wu; Sa Yang; Linlin Liu; Shanshan Li; Pingli Dai; Jing Gao (Science of The Total Environment, 2024)

Biocontrol potential of plant growth-promoting rhizobacteria against plant disease and insect pest - Qinhao Jian; Tongrui Zhang; Yingying Wang; Li Guan; Linlin Li; Longna Wu; Shiyan Chen; Yumei He; Hong Huang; Shugang Tian; Hu Tang; Litang Lu (Antonie van Leeuwenhoek, 2024)

Advancing tea detection with artificial intelligence: Strategies, progress, and future prospects - Qilin Xu; Yifeng Zhou; Linlin Wu (Trends in Food Science & Technology, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Augmenting corn starch gel printability for architectural 3D modeling for customized food - Dongni Xian; Linlin Wu; Keying Lin; Peng Liu; Silin Wu; Yang Yuan; Fengwei Xie (Food Hydrocolloids, 2024)

High-value multilayer graphene oxide prepared by catalytic pyrolysis of petroleum tar and applications: Trash to treasure - Lu Liu; Jialin Wang; Yifei Wu; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemical Engineering Journal, 2024)

The Environmental Niche of the Light Purse Seine Fleet in the Northwest Pacific Ocean Based on Automatic Identification System Data - Shenglong Yang; Lijun Wan; Linlin Yu; Jiashu Shi; Weifeng Zhou; Shengmao Zhang; Fei Wang; Zuli Wu; Yang Dai; Keji Jiang; Wei Fan (Journal of Marine Science and Engineering, 2024)
Ecosystem-based fisheries management requires high-precision fisheries information to provide relevant data for natural resource management, assessment, and marine spatial planning. This study utilizes Automatic Identification System (AIS) data from light purse seine vessels from the Chinese mainland that were collected from May to November between 2020 and 2022, along with the corresponding environmental data. By applying boosted regression trees (BRTs) and generalized additive models (GAMs), this study establishes nonlinear relationships between fishing intensity and predictor variables and explores the ecological and environmental drivers behind the spatial distribution of light purse seine vessels from the Chinese mainland in the Northwest Pacific. This research identifies the key influencing factors and reveals significant seasonal preferences for different marine environments in various months, with chlorophyll-a being the primary influencing factor. The predicted fishing effort closely resembles observed data, providing valuable information to support fisheries resource management and planning.

Exploring the paradox of densification and greening in China’ s old cities - Wenqi Chen; Yuxuan Qiu; Linlin Ruan; Chun Ren; Chunfeng Zhou; Sucheng Xu; Kechao Wang; Tingting He; Wu Xiao (Urban Forestry & Urban Greening, 2024)

3D-printed devices for continuous-flow lithium recovery of brines - Jiangtao Yu; Jie Zhu; Zhuo Han; Peng Cui; Haiying Mi; Anan Zhang; Linlin Chen; Xiaowei Li; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2024)

Source characteristics of the 2006 Pingtung earthquake doublet off southern Taiwan and the possible contribution of submarine landslides to the Tsunami - Gui Hu; Linlin Li; Kenji Satake; Tso-Ren Wu; Peitao Wang; D.J. Doong; Philip L.-F. Liu (Earth and Planetary Science Letters, 2024)

Functional molecules surface segregation engineering in electrospinning: Design, regulation, and applications - Linlin Cao; Chen Qu; Jingchong Liu; Wenhui Li; Lihua Jiang; Boyu Jing; Chuandong Wu; Jiemin Liu (Chemical Engineering Journal, 2024)

SLAM-PYE: Tightly coupled GNSS-binocular-inertial fusion for pitaya positioning, counting, and yield estimation - Hongjie Wang; Xiangyu Hong; Linlin Qin; Chun Shi; Gang Wu (Computers and Electronics in Agriculture, 2024)

An adaptive PID controller for path following of autonomous underwater vehicle based on Soft Actor–Critic - Yuxuan Wang; Yaochun Hou; Zhounian Lai; Linlin Cao; Weirong Hong; Dazhuan Wu (Ocean Engineering, 2024)

Quantify the extensive crop damage and grain losses caused by underground coal mining subsidence in eastern China - Wenqi Chen; Wu Xiao; Tingting He; Linlin Ruan; Yanling Zhao; Zhenqi Hu (Journal of Cleaner Production, 2024)

Spatial diffusion of potentially toxic elements in soils around non-ferrous metal mines - Linlin Li; Yunlong Zhang; Lingyan Zhang; Bo Wu; Xinhong Gan (Environmental Research, 2024)

Long-term non-flooded cultivation with straw return maintains rice yield by increasing soil pH and soil quality in acidic soil - Jingjie Zhou; Sheng Tang; Wankun Pan; Xiu Liu; Kefeng Han; Linlin Si; Qingxu Ma; Xiali Mao; Haoran Fu; Lianghuan Wu (European Journal of Agronomy, 2024)

High-amylose starch-based gel as green adhesive for plywood: Adhesive property, water-resistance, and flame-retardancy - Yaoxing Chen; Yongjing Rao; Peng Liu; Linlin Wu; Guojie Zhang; Jianguo Zhang; Fengwei Xie (Carbohydrate Polymers, 2024)

A bibliometric analysis of blue carbon (1993–2023): evolution of research hot topics and trends - Shanshan Wang; Dandan Yan; Chenhao Wang; Linlin Wu; Yiming Huang (Frontiers in Marine Science, 2024)
Blue carbon refers to the carbon fixed in marine ecosystems such as mangroves, salt marshes, and seagrass beds. Considered a treasure house for capturing and storing carbon dioxide, it can alleviate environmental issues linked to climate change and positively influence the environments where people live. Thus, to clarify the hotspots and development trends of blue carbon research, bibliometric analysis incorporating ScientoPy and VOSviewer software were used to quantitatively analyze 4,604 blue carbon publications from Web of Science and Scopus databases between 1993 and 2023. The results indicate a rapidly growing number of published studies on blue carbon, with blue carbon research being multifaceted and gradually becoming an interdisciplinary and international topic. This study on blue carbon, which is based on keyword clustering analysis, comprises three stages. The analysis of the strength of the cooperative connections between scholars in various countries who have published work on blue carbon. found that the cooperation networks of developed countries are strong and those of developing countries are relatively weak. Quantitative trend analysis reveals a growing focus on the restoration and conservation of blue carbon ecosystems, with remote sensing being the predominant technology used in the blue carbon research field in recent years. In blue carbon research, increasing carbon sequestration capacity, climate change mitigation, and carbon sequestration in macroalgae remain potential hotspots for research and development.

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Spatial distribution and regional tectonic significance of the newly discovered Kalawenguquan fault in the interior of the Tian Shan Mountain Range, Western China - Xingao Li; Zhongtai He; Zhikun Ren; Linlin Li; Lei Wang; Haomin Ji; Xiaoxiao Zhu; Long Guo; Liangliang Wu (Journal of Asian Earth Sciences, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Influence of mixing uniformity between stabilisation materials and contaminated soil on the stabilisation efficiency of heavy metals - Yunlong Zhang; Lixia Sun; Bo Wu; Meng Zhang; Shuhai Guo; Linlin Li; Shuqi Li; Longlong Qu (Journal of Environmental Chemical Engineering, 2024)

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

Review on post-combustion CO2 capture by amine blended solvents and aqueous ammonia - Jiaxing Du; Wu Yang; Linlin Xu; Lei Bei; Siyuan Lei; Wei Li; Haitao Liu; Ben Wang; Lushi Sun (Chemical Engineering Journal, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Mapping Chinese plastic flows from 2001 to 2040 based on dynamic probabilistic material flow analysis and scenario projection - Linlin Xia; Yuhan Ke; Zihao Wu; Jianbing Wang; Ruwei Wang; Yanpeng Cai; Zhifeng Yang (Resources, Conservation and Recycling, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Numerical investigation of microbubble drag reduction on an axisymmetric body based on Eulerian multiphase model - Xuanhao Shao; Ning Liang; Shijie Qin; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Experimental investigation of propeller blade back cavitation induced pressure pulses by synchronous observation - Rui Wu; Heng Liu; Weiqi Chen; Sheng Ji; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Ginsenoside Rk1 induces autophagy-dependent apoptosis in hepatocellular carcinoma by AMPK/mTOR signaling pathway - Huanyan Wu; Linlin Qu; Xue Bai; Chenhui Zhu; Yuan Liu; Zhiguang Duan; Hongyan Liu; Rongzhan Fu; Daidi Fan (Food and Chemical Toxicology, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Mild low-temperature photothermal therapy demonstrated a distinctive 'hot spring' effect in the multichannel regulation of atherosclerosis instead of inducing foam cell apoptosis - Jie Sheng; Ziyue Zu; Jianchen Qi; Yugang Zhang; Haoguang Wu; Zhicheng Wang; Yu Miao; Tao Zheng; Sheng Wang; Linlin Zhang; Guangming Lu; Longjiang Zhang (Chemical Engineering Journal, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Interactive effects of dinotefuran and Nosema ceranae on the survival status and gut microbial community of honey bees - Linlin Liu; Min Shi; Yanyan Wu; Xianbing Xie; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2024)

Multipath diffusion process and spatial accumulation simulation of Cd in lead-zinc mining areas - Linlin Li; Bo Wu; Shuhai Guo; Enzhu Hu; Yunlong Zhang; Lixia Sun; Shuqi Li (Journal of Hazardous Materials, 2024)

Deterioration of single-use biodegradable plastics in high-humidity air and freshwaters over one year: Significant disparities in surface physicochemical characteristics and degradation rates - Lingling Hu; Linlin He; Li Cai; Yumeng Wang; Gang Wu; Daoyong Zhang; Xiangliang Pan; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Kinetics and debromination studies on the pyrolysis of waste printed circuit boards with the addition of copper and copper oxides - Tao Chen; Chuan Ma; Ben Wang; Linlin Xu; Wu Yang; Lushi Sun (Journal of Cleaner Production, 2024)

The miR-34b/MEK/ERK pathway is regulated by NR5A1 and promotes differentiation in primary bovine Sertoli cells - Qibing Tao; Linlin Zhang; Yun Zhang; Mingming Liu; Jie Wang; Qian Zhang; Jiancheng Wu; Aihua Wang; Yaping Jin; Keqiong Tang (Theriogenology, 2024)

Microplastics alter Cr accumulation and fruit quality in Cr(VI) contaminated soil-cucumber system during the lifecycle: Insight from rhizosphere bacteria and root metabolism - Kailin Gong; Qi Zhang; Xuechun Shao; Yonghong Wu; Zhihua Qiao; Linlin Qiu; Wei Zhang; Cheng Peng (Science of The Total Environment, 2024)

Spatio-temporal variability of fishing habitat suitability to tuna purse seine fleet in the Western and Central Pacific Ocean - Shenglong Yang; Lijun Wang; Yingjie Fei; Shengmao Zhang; Linlin Yu; Heng Zhang; Fei Wang; Yumei Wu; Zuli Wu; Wei Wang; Jiayu Shi; Keji Jiang; et al. (Regional Studies in Marine Science, 2024)

An urban metabolism framework purpose to assess the dynamics of linear alkylbenzenes (LABs) discharge flows and driving forces at the city level in Guangdong province, China - Zihao Wu; Linlin Xia; Junye Zhong; Yan Zhang (Environmental Pollution, 2024)

Colorimetric microneedle sensor using deep learning algorithm for meat freshness monitoring - Jie Wang; Linlin Xia; Han Liu; Chong Zhao; Siyu Ming; Jingyi Wu (Chemical Engineering Journal, 2024)

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Study on the late quaternary activity of the Jinyang-Ningnan segment of the Lianfeng fault zone - Liangliang Wu; Zhongtai He; Dongsheng Xu; Linlin Li; Long Guo; Xingao Li (Journal of Structural Geology, 2024)

Acid-assisted ultrasonic preparation of nitrogen-doped MXene quantum dots for the efficient fluorescence “off-on-off” detection of Zn(II) in water and oxalic acid in vegetables - Jinwen Yang; Linlin Chen; Jie Qi; Feili Luo; Lin Li; Honghong Wu; Feifei Cao; Jiangjiang Gu (Food Chemistry, 2024)

One-step, reagent-free construction of nano-enzyme as visual and reusable biosensor for oxidase substrates - Ke Quan; Yuqing Zeng; Wenke Zhang; Fengfeng Li; Mengjiao Li; Zhihe Qing; Linlin Wu (Analytica Chimica Acta, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Effect mechanisms of leading-edge tubercle on blade cavitation control in a waterjet pump - Guoshou Zhao; Ning Liang; Qianqian Li; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2023)

circ_SPEF2 Regulates the Balance of Treg Cells by Regulating miR-16-5p/BACH2 in Lymphoma and Participates in the Immune Response - Jie Zhou; Min Xu; ZhaoZhao Chen; LinLin Huang; ZhuoLin Wu; ZhongPei Huang; Lin Liu (Tissue Engineering and Regenerative Medicine, 2023)

Does environmental policy stringency influence CO2 emissions in the Asia Pacific region? A nonlinear perspective - Linlin Liu; Liwei Pang; Hong Wu; Muhammad Hafeez; Raufhon Salahodjaev (Air Quality, Atmosphere & Health, 2023)

Insight into the mechanisms of neuroendocrine toxicity induced by 6:2FTCA via thyroid hormone disruption - Linlin Wu; Jie Gu; Xinjie Duan; Feng Ge; Heyong Ye; Lingcan Kong; Wenwei Liu; Rong Gao; Jiandong Jiao; Huanhuan Chen; Guixiang Ji (Chemosphere, 2023)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Continuous flow fluorination facilitated by KF assisted by water: From batch to continuous flow - Tao Shen; Chenjun Jiang; Yifeng Lai; Linlin Wu; Liangquan Zhang; Chao Qian (Journal of Fluorine Chemistry, 2023)

A lipidomic approach to bisphenol F-induced non-alcoholic fatty liver disease-like changes: altered lipid components in a murine model - Xinjing Wang; Linlin Wu; Jingxian Tao; Heyong Ye; Jun Wang; Rong Gao; Wenwei Liu (Environmental Science and Pollution Research, 2023)

An ultra-stable high entropy metal nitride for aerobic oxidative desulfurization and source recovery of aromatic sulfides from fuel oils - Peiwen Wu; Chang Deng; Penghui Liu; Feng Liu; Linlin Chen; Bangzhu Wang; Wenshuai Zhu; Chunming Xu (Chemical Engineering Journal, 2023)

Construction of CoTiO3/TiO2/Ti composite catalytic membrane for degradation of tetracycline via peroxymonosulfate activation: Reactive oxygen species and electron transfer pathways - Yi Li; Linlin Wang; Longfei Wang; Weijie Wu; Fangjie Zhang; Haijiao Xie (Chemical Engineering Journal, 2023)

Li-intercalation chemistry of few-layer borophene with ultrahigh capacity and fast kinetics - Linlin Guo; Huili Wang; Zhonghan Wu; Xinru Yang; Ruoxuan Ma; Yanfang Hu; Geng Li; Dongjie Shi; Wei Xie; Wei Zhang; Fujun Lan; Limin Zhou; et al. (Chemical Engineering Journal, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Assessment on the stereoselective behavior of cyflumetofen to earthworms (Eisenia foetida): Degradation, bioaccumulation, toxicity mechanism, and metabolites - Linlin Shi; Chao Shen; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Science of The Total Environment, 2023)

Targeted preparation of biochar for the application as composting additive: Influence mechanism of feedstock properties on biochar derived from traditional Chinese herb residue - Haoyu Tang; Aijun Li; Linlin Yi; Yongda Huang; Qian Deng; Yangwei Wu; Hong Yao (Process Safety and Environmental Protection, 2023)

Geranylgeranylacetone, an inducer of heat shock protein 70, attenuates pulmonary fibrosis via inhibiting NF-κB/NOX4/ROS signalling pathway in vitro and in vivo - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Chemico-Biological Interactions, 2023)

GGA (geranylgeranylacetone) ameliorates bleomycin-induced lung inflammation and pulmonary fibrosis by inhibiting apoptosis and oxidative stress - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Molecular Biology Reports, 2023)

Identifying the O3 chemical regime inferred from the weekly pattern of atmospheric O3, CO, NOx, and PM10: Five-year observations at a center urban site in Shanghai, China - Gen Zhang; Yifeng Sun; Wanyun Xu; Lingyan Wu; Yuseng Duan; Linlin Liang; Yuan Li (Science of The Total Environment, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Strategies for mapping protein hydrolysate profiles and pharmacokinetics based on non-targeted proteomics combining skyline-aided quantitative techniques - Shuying Mao; Wei Jin; Sisi Fu; Keanqi Liu; Feng Xu; Linlin Wu; Yexin Xu; Huizhu Yang; Huafang Liu; Guangji Wang; Yan Liang (Analytica Chimica Acta, 2023)

Seasonal distribution of the early life stages of the small yellow croaker ( Larimichthys polyactis ) and its dynamic controls adjacent to the Changjiang River Estuary - Min Xu; Yihe Wang; Zunlei Liu; Yong Liu; Yi Zhang; Linlin Yang; Fei Wang; Hui Wu; Jiahua Cheng (Fisheries Oceanography, 2023)
The distribution of the early life stages of Larimichthys polyactis indicates the availability of suitable spawning and nursing grounds and enables a better understanding of the distribution of its geographic subpopulations and isolation. Large‐scale quantitative ichthyoplankton surveys of L. polyactis were performed from March to July 2018, and a numerical hydrodynamic model was applied to explore the spatiotemporal distribution and habitats of L. polyactis early life stages adjacent to the Changjiang River Estuary. Two distinct early life stage distribution patterns were found. One occurred during March and April in the deep waters seaward of the Changjiang River bottom plume front, to the east and southeast of the Changjiang River Estuary. The other occurred in May and June throughout the entire water column in coastal waters to the east and north of the Changjiang River Estuary. Rising seasonal temperatures, and the local dynamic processes such as the Changjiang River plume, determined the transitions between the two distribution patterns. A potential fish larval migration route from the southern deep shelf waters to the northern coastal waters within the motor‐trawl prohibition line was suggested. This study contributes to our understanding of the mixture of habitats used by the two L. polyactis subpopulations in the southern Yellow Sea and the East China Sea.

Spatial response relationship between mining and industrial activities and eco-environmental risks in mineral resource–based areas - Yang Li; Lingyan Zhang; Bo Wu; Linlin Li; Yunlong Zhang (Environmental Science and Pollution Research, 2023)

Systematic assessment of cyflumetofen toxicity in soil-earthworm (Eisenia fetida) microcosms - Linlin Shi; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Journal of Hazardous Materials, 2023)

Occurrence, sources and risk of heavy metals in soil from a typical antimony mining area in Guizhou Province, China - Yuting Guo; Rongshan Wu; Changsheng Guo; Jiapei Lv; Linlin Wu; Jian Xu (Environmental Geochemistry and Health, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Atomic-level chemical reaction promoting external quantum efficiency of organic photomultiplication photodetector exceeding 108% for weak-light detection - Linlin Shi; Yizhi Zhu; Guohui Li; Ting Ji; Wenyan Wang; Ye Zhang; Yukun Wu; Yuying Hao; Kaiying Wang; Jun Yuan; Yingping Zou; Beng S. Ong; et al. (Science Bulletin, 2023)

Cloning and expression of the mitochondrial cytochrome c oxidase subunit II gene in Sitophilus zeamais and interaction mechanism with allyl isothiocyanate - Linlin Jiang; Yue Li; Weilin Shi; Wei Chen; Zhiqing Ma; Juntao Feng; Ahmed S. Hashem; Hua Wu (Pesticide Biochemistry and Physiology, 2023)

Source apportionment of heavy metals in the soil at the regional scale based on soil-forming processes - Bo Wu; Linlin Li; Shuhai Guo; Yang Li (Journal of Hazardous Materials, 2023)

Long-term performance study applying a tandem AnSBR-ASBR to treat wastewater containing N, N-dimethylformamide: Sludge physicochemical properties, microecology, and functional genes - Linlin Cao; Chengyuan Su; Yiying Lu; Jinyan Wu; Lixin Wei; Junjie Liao; Yunchuan Xian; Shu Gao (Journal of Environmental Chemical Engineering, 2023)

MOF-templated fabrication of Ni@C/g-C3N4 catalyst with high-dense accessible active sites achieving dicyclopentadiene hydrogenation at ambient conditions and comprehensive mechanism insight - Chenghong Wu; Xiaopeng Chen; Jiezhen Liang; Jiawei Fu; Zhongyao Zhang; Xiaojie Wei; Linlin Wang (Chemical Engineering Journal, 2023)

A Tiered Ecological Risk Assessment of Caffeine by Using Species Sensitivity Distribution Method in the Nansi Lake Basin - Lei Zheng; Juan Zhang; Yinan Wu; Linlin Li; Junhong Ling; Sai Wang; Wenlong Yang; Yezhu Yin; Liang Dong; Yizhang Zhang (Bulletin of Environmental Contamination and Toxicology, 2023)

Comprehensively investigating performance and potential mechanism of anammox-based nitrogen removal process with different microbial morphologies under mainstream conditions - Shuang Liu; Xinxin Xu; Hongli Li; Ming Zeng; Linlin Hao; Ruihua Zhao; Jingguo Cao; Nan Wu; Zongpeng Zhang (Journal of Environmental Chemical Engineering, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Sustainable estuarine governance based on artificial island scheme for a highly anthropogenic influenced Shenzhen Bay, China - Wanrong Wu; Linlin Wang; Xiaoyu Lei; Yang Zheng; Jie Wei; Xian-zhong Mao (Journal of Hydrology, 2023)

A decision-support system for recycling of residents’ waste plastics in China based on material flow analysis and life cycle assessment - Manzhi Liu; Jixin Wen; Linlin Zhang; Jixin Wu; Xiaotao Yang; Ying Qin; Yingjie Liu (Environmental Science and Pollution Research, 2022)

Surveillance of long-term environmental elements and PM2.5 health risk assessment in Yangtze River Delta, China, from 2016 to 2020 - Keqin Wu; Yuanhua Meng; Yan Gong; Xuhui Zhang; Linlin Wu; Xinliang Ding; Xiaofeng Chen (Environmental Science and Pollution Research, 2022)

Abnormal Level of Manganese, Iron, Iodine, and Selenium in the Hair of Children Living in Kashin–Beck Disease Endemic Areas - Feng’e Zhang; Cuiyan Wu; Pan Zhang; Xi Wang; Peilin Meng; Sijia Tan; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Drinking water elements constituent profiles and health risk assessment in Wuxi, China - Keqin Wu; Yuanhua Meng; Yan Gong; Linlin Wu; Wenwei Liu; Xinliang Ding (Environmental Monitoring and Assessment, 2022)

QpefBD: A Benchmark Dataset Applied to Machine Learning for Minute-Scale Quantitative Precipitation Estimation and Forecasting - Anyuan Xiong; Na Liu; Yujia Liu; Shulin Zhi; Linlin Wu; Yongjian Xin; Yan Shi; Yunjian Zhan (Journal of Meteorological Research, 2022)

Taxonomy and regeneration of a newly recorded Polychaete Capitella teleta (Annelida, Capitellidae) in the coastal water of Shandong, China - Qian Li; Yongnan Li; Yue Wang; Xuwen Wu; Linlin Zhang (Journal of Oceanology and Limnology, 2022)

Deep convolutional neural network with random field model for lake ice mapping from Sentinel-1 imagery - Zhiguo Ma; Zihao Liu; Jiabin Pu; Linlin Xu; Kui Li; Linglong Wangqu; Rui Wu; Yiyi Ma; Ye Chen; Claude Duguay (International Journal of Remote Sensing, 2021)

A leucoanthocyanidin dioxygenase gene (RtLDOX2) from the feral forage plant Reaumuria trigyna promotes the accumulation of flavonoids and improves tolerance to abiotic stresses - Ningning Li; Xue Wang; Binjie Ma; Zhigang Wu; Linlin Zheng; Zhi Qi; Yingchun Wang (Journal of Plant Research, 2021)

Spring phenology outweighed climate change in determining autumn phenology on the Tibetan Plateau - Jie Peng; Chaoyang Wu; Xiaoyue Wang; Linlin Lu (International Journal of Climatology, 2021)
As the third pole of the Earth, the Tibetan Plateau (TP) is highly sensitive to climate change. Phenological changes in spring (i.e., the start of the growing season, SOS) over the TP are of much debate, while our understanding on the variation of autumn phenology (i.e., the end of the growing season, EOS) is still lacking. Given the significance of tracing the latest variation of EOS induced by the ongoing global change, we used the currently longest time series (1982–2018) of the normalized difference vegetation index of the Long Term Data Record from the Advanced Very High Resolution Radiometer (AVHRR LTDR NDVI) and investigated the responses of EOS to biological and climatic factors. We found that the EOS showed an insignificantly delayed trend at an average rate of 0.14 days·decade −1 on the TP. This variation was found for all vegetation types except for alpine sparse vegetation. We further showed that spring SOS had the largest contribution to the interannual variations in EOS, where 46.5% of the vegetated areas showed significantly positive correlations between SOS and EOS ( p

PbrPOE21 inhibits pear pollen tube growth in vitro by altering apical reactive oxygen species content - Ming Qian; Linlin Xu; Chao Tang; Hao Zhang; Hongru Gao; Peng Cao; Hao Yin; Lei Wu; Juyou Wu; Chao Gu; Shaoling Zhang (Planta, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Action of Akt Pathway on La-Induced Hippocampal Neuron Apoptosis of Rats in the Growth Stage - Jinting Wang; Tianwei Wu; Lan Ma; Ying Guo; Yali Huang; Linlin Zheng (Neurotoxicity Research, 2020)

DNA Methylation Analysis of the NR3C1 Gene in Patients with Schizophrenia - Linlin Liu; Jian Wu; Lili Qing; Jiajue Li; Hao Yang; Aicen Ji; Ming Yan; Liping Hu; Shengjie Nie (Journal of Molecular Neuroscience, 2020)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Assessment of the effects of lethal and sublethal exposure to dinotefuran on the wheat aphid Rhopalosiphum padi (Linnaeus) - Denghui Deng; Wenbo Duan; Hao Wang; Kun Zhang; Jianglong Guo; Linlin Yuan; Likui Wang; Shaoying Wu (Ecotoxicology, 2019)

Luteolin decreases the yield of influenza A virus in vitro by interfering with the coat protein I complex expression - Haiyan Yan; Linlin Ma; Huiqiang Wang; Shuo Wu; Hua Huang; Zhengyi Gu; Jiandong Jiang; Yuhuan Li (Journal of Natural Medicines, 2019)

Effect of polysaccharides extracted from Sipunculus nudus (SNP) on the lifespan and immune damage repair of Drosophila melanogaster exposed to Cd (VI) - Jie Su; Linlin Jiang; Jingna Wu; Zhiyu Liu; Yuping Wu (Natural Product Research, 2018)

Linkage disequilibrium and functional analysis of PRE1 insertion together with SNPs in the promoter region of IGFBP7 gene in different pig breeds - Qingyan Wu; Hao Yu; Wenzhen Wei; Yunyun Cheng; Shan Huang; Hongyu Shi; Songcai Liu; Jichao Xia; Hongyao Jia; Linlin Hao (Journal of Applied Genetics, 2018)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Phosphatidylinositol 3-phosphate, an essential lipid in Phytophthora sojae, enriches in the haustoria during infection - Linlin Chen; Wen Wang; Ying Hou; Yuren Wu; Honglian Li; Daolong Dou (Australasian Plant Pathology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Bioavailability of riverine dissolved organic carbon and nitrogen in the Heilongjiang watershed of northeastern China - Jianhong Shi; Hongyang Cui; Liming Jia; Linlin Qiu; Yue Zhao; Zimin Wei; Junqiu Wu; Xin Wen (Environmental Monitoring and Assessment, 2016)

The effects of commercial microbial agents (probiotics) on phytoplankton community structure in intensive white shrimp (Litopenaeus vannamei) aquaculture ponds - Betina Lukwambe; Linlin Qiuqian; Jinfeng Wu; Demin Zhang; Kai Wang; Zhongming Zheng (Aquaculture International, 2015)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

A comparison of de-noising methods for differential phase shift and associated rainfall estimation - Zhiqun Hu; Liping Liu; Linlin Wu; Qing Wei (Journal of Meteorological Research, 2015)

Identification and characteristics of imipenem-resistant Acinetobacter baumannii in surgical wards in a Chinese university hospital - Dalin Wang; Linlin Ma; Zhenyu Wu; Mingcheng Li; Xiaohan Li; Wei Zhang; Kun Chen (Infectious Diseases, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Full and ideal mixing behavior between Zr–Wd (K2ZrSi3O9) and Ti–Wd (K2TiSi3O9): evidences from mineral chemistry, X-ray diffraction pattern and Raman spectrum - Linlin Chang; Xi Liu; Chunming Wu; Xiaoyang Liu; Guowu Li (Physics and Chemistry of Minerals, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Microarray gene expression analysis of Monochamus alternatus (Coleoptera: Cerambycidae) after treatment with a sublethal dose of chloramine phosphorus - Tong Lin; Linlin Luo; Chunmei Wei; Huajun Wu (Applied Entomology and Zoology, 2014)

Transcriptomic analysis reveals key regulators of mammogenesis and the pregnancy-lactation cycle - YuanYuan Zhou; Wei Gong; JingFa Xiao; JiaYan Wu; LinLin Pan; XiaoNuan Li; XuMin Wang; WeiWei Wang; SongNian Hu; Jun Yu (Science China Life Sciences, 2014)

Isolation and characterization of a Δ1-pyrroline-5-carboxylate synthetase (NtP5CS) from Nitraria tangutorum Bobr. and functional comparison with its Arabidopsis homologue - Linlin Zheng; Zhenhua Dang; Haoyu Li; Huirong Zhang; Shubiao Wu; Yingchun Wang (Molecular Biology Reports, 2014)

Lanthanum chloride impairs spatial learning and memory and downregulates NF-κB signalling pathway in rats - Linlin Zheng; Jinghua Yang; Qiufang Liu; Fei Yu; Shengwen Wu; Cuihong Jin; Xiaobo Lu; Lifeng Zhang; Yanqiu Du; Qi Xi; Yuan Cai (Archives of Toxicology, 2013)

Decreased expression of the DBC2 gene and its clinicopathological significance in breast cancer: correlation with aberrant DNA methylation - Linlin Han; Lin Hou; Jinlian Song; Dongliang Lin; Li Wu; Yinlin Ge; Zhongliang Ma (Biotechnology Letters, 2013)

High-Level Expression of Sporamin in Transgenic Chinese Cabbage Enhances Resistance Against Diamondback Moth - Lin Qiu; Tingting Wu; Heng Dong; Linlin Wu; Jiashu Cao; Li Huang (Plant Molecular Biology Reporter, 2013)

PEGylated Multi-Walled Carbon Nanotubes for Encapsulation and Sustained Release of Oxaliplatin - Linlin Wu; Changjun Man; Hong Wang; Xiaohe Lu; Qinghai Ma; Yu Cai; Wanshan Ma (Pharmaceutical Research, 2013)

Heavy metal contamination in the marine organisms in Yantai coast, northern Yellow Sea of China - Gaosheng Zhang; Dongyan Liu; Huifeng Wu; Linlin Chen; Qingxi Han (Ecotoxicology, 2012)

Left ventricular hypertrophy induced by abdominal aortic banding and its prevention by angiotensin receptor blocker telmisartan—a proteomic analysis - Li Liu; Wen Wang; Xianmin Meng; Jiuming Gao; Haiying Wu; Peihe Wang; Weichun Wu; Linlin Wang; Liyuan Ma; Weiguo Zhang (Journal of Physiology and Biochemistry, 2010)